What are the optimal ways of working in delivering orthotic interventions to enhance rehabilitation outcomes and reduce complications for stroke survivors?: establishing National Statements of Best Practice - Golding-Day, Miriam (2025)
Background Stroke is the leading cause of adult disability in the UK with two thirds of stroke survivors leaving hospital with ongoing functional deficit. For many stroke survivors regaining mobility is a key aim in their rehabilitation, and orthotics have a crucial role to play in achieving this. There are up to two million orthotic users in the UK and with the predicted increase in prevalence of stroke by 60% in the next 10 years, this number is also expected to rise significantly.